2011
DOI: 10.1121/1.3557041
|View full text |Cite
|
Sign up to set email alerts
|

A waveguide invariant adaptive matched filter for active sonar target depth classification

Abstract: This paper addresses depth discrimination of a water column target from bottom clutter discretes in wideband active sonar. To facilitate classification, the waveguide invariant property is used to derive multiple snapshots by uniformly sub-sampling the short-time Fourier transform (STFT) coefficients of a single ping of wideband active sonar data. The sub-sampled target snapshots are used to define a waveguide invariant spectral density matrix (WI-SDM), which allows the application of adaptive matched-filterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, in CAS signals the direct arrival is almost always overlapping in time with the target echo return, and the standard time-gating technique is insufficient to isolate the echo return in the raw acoustic data. Matched filtering may be used to effectively compress the echo pulses so that timegating can isolate the target returns, and it has been shown that the waveguide invariant striations are preserved in matched filter output of PAS signals [3], [5], [17], [18]. However, target motion during the long duty cycle of CAS waveforms will impose some motion-dependent modulation on the target return, which may reduce correlation between the echo return and the source replica.…”
Section: B Extracting the Target Echo In Cas Datamentioning
confidence: 99%
“…However, in CAS signals the direct arrival is almost always overlapping in time with the target echo return, and the standard time-gating technique is insufficient to isolate the echo return in the raw acoustic data. Matched filtering may be used to effectively compress the echo pulses so that timegating can isolate the target returns, and it has been shown that the waveguide invariant striations are preserved in matched filter output of PAS signals [3], [5], [17], [18]. However, target motion during the long duty cycle of CAS waveforms will impose some motion-dependent modulation on the target return, which may reduce correlation between the echo return and the source replica.…”
Section: B Extracting the Target Echo In Cas Datamentioning
confidence: 99%
“…The data-based method for moving target depth estimation is also demonstrated experimentally [ 5 ]. Goldhahn [ 6 ] proposed a waveguide invariant depth classification method based on adaptive matched-filtering under uncertain environmental conditions. Matched field processing (MFP) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] is a generalized beamforming method which uses the spatial complexities of acoustic fields in an ocean waveguide to estimate the range, depth and azimuth of targets.…”
Section: Introductionmentioning
confidence: 99%
“…Yang adopted a method based on eigenvector decomposition technique [ 18 ] and data-based method [ 19 ] for depth estimation. Goldhahn [ 20 ] proposed a method for depth classification based on waveguide invariant adaptive matched-filtering. Matched field processing (MFP) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] has also been widely used in depth estimation studies.…”
Section: Introductionmentioning
confidence: 99%